Targeted K‐Edge Nanoprobes From Praseodymium and Hafnium for Ratiometric Tracking of Dual Biomarkers using Spectral Photon Counting CT - Nivetha Gunaseelan; Parikshit Moitra; Pranay Saha; Teresa Aditya; Mahdieh Moghiseh; Kevin Jonker; Steven Gieseg; Anthony Butler; Fadia Kamal; Dipanjan Pan (Advanced Science)
Abstract Utilizing metal nanoprobes with unique K‐edge identities to visualize complementary biological activities simultaneously can provide valuable information about complex biological processes. This study describes the design and preparation of an innovative pair of K‐edge metal nanoprobes and demonstrates the feasibility of their simultaneous quantitative detection using spectral photon‐counting computed tomography (SPCCT). Glycosaminoglycan (GAG) capped nanoparticles (ca. 15–20 nm) targeting two distinct components of the cartilage tissue, namely, aggrecan (acan) and aggrecanase (acanase) are designed and synthesized. These targeted nanoparticles comprised of praseodymium (Pr) and hafnium (Hf), with well‐separated K‐edge energies, enable simultaneous and ratiometric imaging of dual biomarkers in cartilage tissue. Following extensive physico‐chemical characterization of the ligand‐targeted particles, the feasibility of homing dual biomarkers in vitro is demonstrated. The material discrimination and simultaneous quantification of these targeted particles are also achieved and corroborated with inductively coupled plasmon spectroscopy. For the first time, the use of praseodymium is reported as a contrast agent for SPCCT imaging and demonstrates the ability to pair it with hafnium nanoprobes for multicontrast imaging of diseases. Importantly, the potential for ratiometric molecular imaging and tracking of osteoarthritis (OA) progression is shown with SPCCT K‐edge based imaging approach.